PENGARUH PENAMBAHAN CaCO3 SEBAGAI FILTER PADA SEMEN OPC (ORDINARY PORTLAND CEMENT) TERHADAP PERFORMA SETTING TIME DAN KUAT TEKAN (STUDI KASUS PT. SEMEN INDONESIA) - Sefrilita Risqi Adikaning Rani; Nurlailiyah Isnaini (Universitas Islam Negeri Alauddin Makassar, 2020)
Research has been carried out on the effect of adding CaCO3 as a filler in OPC cement (Ordinary Portland Cement) on setting time performance and compressive strength. The purpose of this study was to determine the effect of adding CaCO3 as a filler on the compressive strength and setting time of OPC cement. The principle of this experiment is the addition of CaCO3 to each of the OPC cement samples, after which the paste is tested for setting time with the Vicat tool. Mortar samples were made to be tested for compressive strength using a compressive strength test equipment. The results of the addition of CaCO3 as a filler in OPC cement include, the optimum value was obtained when the addition of CaCO3 was 5.5% based on the results of linear interpolation with a blank ratio. However, it is safer if the optimum value used as a reference for PT Semen Indonesia (Persero)Tbk is 5.4%. The addition of CaCO3 to OPC cement can save production costs in making OPC cement. The value of setting time and compressive strength obtained still meet the standards set by PT Semen Indonesia (Persero) Tbk.